Providing Dynamic Update in an Operating System - Baumann, Andrew; Heiser, Gernot; Appavoo, Jonathan; Silva, Dilma Da; Krieger, Orran; Wisniewski, Robert W.; Kerr, Jeremy (Proceedings of the 2005 Annual USENIX Technical Conference, 2005)
Dynamic update is a mechanism that allows software updates and patches to be applied to a running system without loss of service or down-time. Operating systems would benefit from dynamic update, but place unique demands on any implementation of such features. These demands stem from the event-driven nature of operating systems, from their restricted run-time execution environment, and from their role in simultaneously servicing multiple clients. We have implemented a dynamic update mechanism in the K42 research operating system, and tested it using previous modifications of the system by kernel developers. Our system supports updates changing both kernel code and data structures. In this paper we identify requirements needed to provide a dynamically updatable operating system, describe our implementation, and present our experiences in designing and using the dynamic update mechanism. We also discuss its applicability to other operating systems.